Social Work Practice Across Disability. - Rothman, Juliet (London : Taylor and Francis, 2018)
"This book will help prepare the reader to work across disabilities by providing knowledge and training grounded within the ecological framework in four principal areas. The four principal areas reader will be trained in are: the societal environment and disability; disability and the individual experience; essential skills for social work micro, mezzo, and macro practice with people with disabilities; and the resource and support network for persons with disabilities. The book is organized around four units, each of which addresses one of the areas noted. It is not the purpose of this book to enable the reader to gain expertise in any one disabling condition or impairment. Rather, the goal is to provide a broad base of knowledge and skills, which will enable the reader to work effectively across a variety of disabling conditions. Special educators, social workers, parents"--Provided by publisher.
Chapter Introduction / Juliet Rothman -- part I The Societal Framework / Juliet Rothman -- chapter 1 Theoretical Frameworks / Juliet Rothman -- chapter 2 An Historical Perspective / Juliet Rothman -- chapter 3 The Disability Rights Movement in the United States / Juliet Rothman -- chapter 4 Disability Legislation and the ada / Juliet Rothman -- chapter 5 Disability Demographics / Juliet Rothman -- part II The Individual Framework / Juliet Rothman -- chapter 6 Using Disability Groupings to Understand Individual Experience / Juliet Rothman -- chapter 7 Disability and Identity Development / Juliet Rothman -- chapter 8 Understanding the Lived Experience -- Onset, Course, and Outcome / Juliet Rothman -- chapter 9 Understanding the Lived Experience -- Living with Limitations and Stereotypes / Juliet Rothman -- chapter 10 Understanding the Lived Experience -- Three Vulnerable Populations / Juliet Rothman -- part III Skills for Social Work Practice / Juliet Rothman -- chapter 11 Using Client Strengths and Worker Skills to Optimize Communication and Relationship / Juliet Rothman -- chapter 12 Assessing Individuals and Communities / Juliet Rothman -- chapter 13 Practice Models -- Working with Individuals / Juliet Rothman -- chapter 14 Practice Models -- Working within the Disability Community / Juliet Rothman -- chapter 15 Practice Models -- Disability as a Social and Political Concern / Juliet Rothman -- part IV The Disability Resource and Support Network / Juliet Rothman -- chapter 16 Overview of Network and Services in the Public Sector / Juliet Rothman -- chapter 17 Overview of Network and Services in the Private Sector / Juliet Rothman -- chapter 18 Public and Private Intersections in Healthcare / Juliet Rothman -- chapter 19 Public and Private Intersections in Housing and Personal Care Needs / Juliet Rothman -- chapter 20 Public and Private Intersections in Employment and Income Support / Juliet Rothman -- chapter 21 The Social Support and Recreation Network / Juliet Rothman -- chapter 22 Mobility, Access, and Adaptive Technology / Juliet Rothman.
OCLC-licensed vendor bibliographic record.
Keywords: Social work with people with disabilities